Implementasi Asas Strict Liability Atas Tanggungjawab Produk Dalam Hukum Perlindungan Konsumen: Studi Perbandingan Antara Indonesia & Amerika Serikat - Pratama, Ridwan Yoga (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Indonesian Consumer Protection Law is based on principles that apply to both consumers and producers. The study found that while there is a great opportunity for the principle of fault-based liability to be changed to strict liability, constraints stand out. Furthermore, the findings show that although Indonesia has started to adopt the principle of strict liability in its consumer protection law, there is still a slight interpretation bias in its legal practice, particularly in the enforcement system. This can be inferred by the fact that “reverse proof” is still used in many legal practices. This is different if we compare it with what has happened in the United States. The United States has fully utilized the principle of absolute liability in its consumer protection legal system. In fact, the United States has used absolute liability with the expansion of intentional tort, which is more favorable to consumers.